Resiko Terjadinya Kejahatan Transnasional Pencucian Uang dalam Kebijakan Carbon Trading: Cindy Dewu*, Saskia Nina Sartori, Ufran - Cindy Dewu; Saskia Nina Sartori; Ufran (Samudra Publisher, 2024)
This research aims to determine and analyze the risk of transnational money laundering crimes in carbon trading policies. Carbon trading is intended to overcome environmental damage, but it can raise the risk of fraud in the field of carbon trading. Apart from the risk of fraud, carbon trading is also vulnerable to money laundering, namely where funds obtained legally and illegally are used to buy turbines and solar panels in developing countries where supervision is weak, as well as problems with the auditors employed. Even the auditors employed to commit this crime often involve auditors from third parties. Even though OJK regulations already exist, these regulations are still inadequate. So there is a blurring of norms in carbon trading